ChemInform Abstract: Eu2+ Luminescence in Ca3Si2O7 and Spectral Widening and Tuning of Eu2+ Emission Color (Orangish‐Red to Green) by Crystal Chemical Substitution. Issue 52 (6th December 2016) - Kasturi, S.; Sivakumar, V.
Abstract: A series of yellowish‐orange emitting phosphors Ca3‐x Eux Si2 O7 (x = 0.0025—0.03) and Ca2.985‐y Mgy Eu0.015 Si2 O7 (y = 0—1) are prepared by calcination of stoichiometric amounts of CaCO3, Eu2 O3, Mg(NO3 )2 and SiO2 in air (1250 °C, 6 h) followed by heating of the as‐prepared material in a 5%H2 /N2 atmosphere (1275 °C, 6 h).